2007
DOI: 10.1016/j.vaccine.2006.12.051
|View full text |Cite
|
Sign up to set email alerts
|

Construction and analysis of variants of a polyvalent Lyme disease vaccine: Approaches for improving the immune response to chimeric vaccinogens

Abstract: There is currently no Lyme disease vaccine commercially available for use in humans. Outer surface protein C (OspC) of the Borrelia has been widely investigated as a potential vaccinogen. At least 38 OspC types have been defined. While the antibody response to OspC is protective, the range of protection is narrow due to the localization of protective epitopes within OspC type-specific domains. To develop a broadly protective vaccine, we previously constructed a tetravalent chimeric vaccinogen containing epitop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
40
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 55 publications
2
40
0
1
Order By: Relevance
“…The goal of our efforts is to develop a chimeric polyvalent vaccine construct that consists of the type-specific, protective epitopes of those OspC types associated with invasive infection in humans. As proof of principle, we previously developed a construct that incorporates epitopes from OspC types A, B, K, and D (11)(12)(13). This construct elicited bactericidal antibody against spirochetes ex-FIG.…”
mentioning
confidence: 99%
“…The goal of our efforts is to develop a chimeric polyvalent vaccine construct that consists of the type-specific, protective epitopes of those OspC types associated with invasive infection in humans. As proof of principle, we previously developed a construct that incorporates epitopes from OspC types A, B, K, and D (11)(12)(13). This construct elicited bactericidal antibody against spirochetes ex-FIG.…”
mentioning
confidence: 99%
“…One possible approach to consider is the development of a chimeric FhbB protein harboring the major FhbB types. The utility of chimeric proteins to elicit bactericidal Ab against diverse strains of the Lyme disease spirochetes has been demonstrated in several studies (41)(42)(43). It may also be possible to exploit Ab directed at FhbB as a therapeutic tool for periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…The OspA vaccine was demonstrated to be safe, but it was withdrawn from the market only a few years after introduction, as acceptance by the public was low because of a number of factors (38)(39)(40)(41). Several candidate vaccines investigated more recently have targeted proteins produced in abundant amounts by B. burgdorferi grown in the laboratory and some that are exposed on the bacterial surface, although only some of these proteins have also been assigned activities or functions in vitro and/or in vivo (6,8,(42)(43)(44)(45)(46)(47)(48). An immune response that blocks the function of a protein may prove more efficacious in preventing disease than a response that does not interfere with function.…”
Section: Discussionmentioning
confidence: 99%
“…A single dose of lyophilized whole-cell Borrelia produced limited protection as a vaccine in hamsters (4,5), and the authors suggested that further studies were warranted. In fact, whole-cell vaccines are currently available for veterinary use, but a less reactogenic multivalent subunit vaccine has more recently been developed (6)(7)(8). Live attenuated flagellumless Borrelia cells in a high-passage-number noninfectious background also elicited protective immunity in mice for a limited duration (9).…”
mentioning
confidence: 99%